PERAN MAHASISWA DALAM PENGEMBANGAN USAHA PERIKANAN IKAN LELE PADA MASA PANDEMI COVID-19 MELALUI PROGRAM KULIAH KERJA NYATA - Hatiningsih, Sayi; Ditama, I.K.N.; Diantara, I.K.W.; Wirawan, I.K.G.S.; Puspasari, D.A.D.; Rupayasa, N.M.J.A.D.; Pratama, P.B.A.; Puteri, N.P.Y.A. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana Mengabdi, 2022)
Kekeran Village is one of the villages producing freshwater fish in Bali. Kekeran Village is one of the villages in Mengwi sub-district, Badung regency. Catfish is a freshwater fish commodity that is widely cultivated in Kekeran Village. On the other hand, the Covid-19 pandemic has provided various changes in all areas of life in Bali, especially the economy. Many private businesses in Bali such as restaurants and hotels reduction or suffered losses. This correlates with a decrease in consumer demand for freshwater fish, especially catfish. Therefore, support is needed from various parties to solve the impact of Covid-19. One of them is through the Kuliah Kerja Nyata program organized by the university and carried out by students. This community service activity with students aims to provide knowledge, and appropriate technology in developing catfish business to the community in Kekeran Village. The result of dedication shown that the developing catfish business has been going well. People of Kekeran Village, especially Tunjung Putih Group were very enthusiastic in following the training and assistance. The evaluation show that the activity is beneficial to the community because it can improve information and knowledge of the community.   Keywords: Kekeran Village, pandemic Covid-19, KKN Tematik, student role, catfish